Copovidone-related Cutaneous Response in the Dog. (January 2017) - Morgan, Sherry J.; Besenhofer, Lauren M.; Buck, Wayne; Lorenz, Helga; Rhodes, James W.; Yang, Yi
A cutaneous response (localized swelling and/or erythema of the skin) has been noted in dog toxicology studies in which multiple, unrelated compounds were administered orally with copovidone as a vehicle. The response has been noted in studies with 6 different test items that are structurally unrelated and span several different therapeutic indications spanning an approximate 6-year period (2009–2015). A factor common among the studies is the formulation—a copovidone amorphous solid dispersion (ASD). Cutaneous responses have not been observed in dogs administered non-ASD formulations of the same test items but have occasionally been noted in placebo (copovidone control) dogs. Polyvinylpyrrolidone (a polymer of one of the primary components of copovidone) has been reported to result in similar findings in dogs when administered by the intravenous route. Considerations for the role of copovidone and the potential role of histamine in the cutaneous changes are outlined.